Sydney was asked whether the following equation is an identity: (2x^2-18)(x+3)(x-3)=2x^4-36x^2+162

Question

Sydney was asked whether the following equation is an identity: (2x^2-18)(x+3)(x-3)=2x^4-36x^2+162

in progress 0
Iris 1 week 2021-09-13T09:35:55+00:00 2 Answers 0

Answers ( )

    0
    2021-09-13T09:37:44+00:00

    Answer:

    Yes it is.

    See below.

    Step-by-step explanation:

    (2x^2-18)(x+3)(x-3)

    = (2x^2 – 18(x^2 – 9)

    = 2x^4 – 18x^2 – 18x^2 + 162

    = 2x^4 – 36x^2 + 162.

    The left side transforms to the right side so it is an identity.

    0
    2021-09-13T09:37:46+00:00

    Answer:

    Any value of x x makes the equation true. All real numbers Interval Notation: ( − ∞ , ∞ )
    .

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )